A Comparative Study on Acoustic Characteristics of Methane and Tetrahydrofuran Hydrate-Bearing Sediments - Wengao Zhao; Qingtao Bu; Zihao Wang; Tong Liu; Qingguo Meng; Yapeng Zhao; Gaowei Hu (Journal of Marine Science and Engineering, 2024)
Laboratory acoustic measurements of hydrate-bearing sediments serve as an important reference for the geological interpretation of seismic exploration data. Tetrahydrofuran (THF) hydrates are relatively easy to form with precise control of hydrate saturation, and they overcome the long time it takes for methane in sediments to form hydrate. However, when THF hydrates are used as a substitute for methane hydrate, their acoustic properties yield different results. This study reports the results of a series of laboratory experiments on the formation of methane and THF hydrate in quartz sand and the evaluation of their acoustic properties. It compares the experimental results with the results of calculations from micro-distribution models of the four hydrates using effective medium theory (EMT). Methane hydrate formed by the excess gas method has higher acoustic velocities than THF hydrate at 0–80% saturation, but at 80–100% saturation, the situation reverses, with THF hydrate having a higher wave velocity. The methane hydrate synthesis process follows a mixed micro-distribution, with grain coating predominating at low saturations, the pore-filling mixing mode dominating at medium saturations, and grain coating dominating at high saturations. In addition, THF hydrate has a slow-velocity growth at low saturation and is dominated by a pore-filling model and a load-bearing model at high saturation. We compared our experimental data with a compilation of similar published results to confirm their reliability and support our conclusions. Both hydrate types exhibit distinct micro-distributions across different saturations. Therefore, when testing the elastic characteristics of hydrate sediments, the distinct hydrate synthesis methods and micro-distribution should be considered, especially when using THF hydrate as an alternative to methane hydrate.